Supporting Holistic Student Development Through Online Community Building - Borowiec, Katrina; Kim, Deoksoon; Wang, Lizhou; Kim, Julie; Wortham, Stanton (Online Learning, 2021)
Faculty members abruptly transitioned to online course delivery during the COVID-19 public health crisis. Unfortunately, the isolation of learning online had the potential to damage students’ well-being during an already stressful pandemic. Furthermore, many faculty members had little experience with online modes of instruction and few effective strategies for building community online. This exploratory sequential mixed methods study uses data from 37 individual interviews with faculty across diverse disciplines, course evaluations from 13 of the 37 interview participants, and survey data from 347 faculty to answer the following research question: How did faculty foster a sense of community online to support students’ holistic well-being during the COVID pandemic? What strategies can faculty use to create community and foster well-being in online courses? Results show that successful strategies centered around intentional and purposeful course design, establishing clear expectations for faculty and students, and fostering supportive and trustworthy online learning environments.